MNEs' regional headquarters and their CSR agenda in the African context. Issue 5 (14th September 2015) - Pervez N. Ghauri, Professor Byung II Park; Dr Chang Hoon Oh, Professor; Gruber, Verena; Schlegelmilch, Bodo B.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Corporate social responsibility (CSR) initiatives can provide a mechanism for tapping into the vast consumer markets of developing countries. The purpose of this paper is to investigate how regional headquarters (RHQs) of multinational enterprises (MNEs) in Africa pursue CSR and whether their initiatives are aligned with their own global CSR agendas or tailored to local idiosyncrasies. Design/methodology/approach – Following a secondary data analysis of MNEs' CSR and sustainability reports and their homepages, in-depth interviews with their CSR managers in African RHQs are conducted. Findings – The paper provides insights into motivations of RHQs to pursue specific CSR initiatives. MNEs need to make considerable adaptations to their global CSR agendas in order to develop initiatives that fit the local setting. The authors further identify key institutions in developing countries and discuss the potential of collaborations with MNEs in their CSR initiatives. Research limitations/implications – Future research should assess the impact of environmental differences (e.g. developing nations compared to industrialized nations) and firm characteristics on CSR autonomy (both at RHQs and at the subsidiary level). Furthermore, the perspectives of the various stakeholders (such as local governments or NGOs) should be examined to establish a holistic understanding of CSR in developing countries. Practical implications – MNEs gain a better understanding of peculiarities encountered in developing countries and are provided with recommendations on how to develop their CSR policies. Social implications – The paper directs awareness to CSR in the African context, thereby providing a platform for understanding some of this continent's most important challenges. Originality/value – The paper shows how the context of developing countries shapes the translation process of MNEs' global CSR agendas. Companies benefit from the best practice examples provided in this paper and learn from the stakeholder collaborations discussed.